Do High and Volatile Levels of Public Investment Suggest Misconduct? The Role of Institutional Quality - Grigoli, Francesco; Mills, Zachary (2012)
This paper investigates the impact of institutional quality on public investment levels over the period 1984-2008. Moreover, it studies how the volatility of public investment and the quality of infrastructure are affected by institutional quality, and explores the contribution of other critical factors. The findings suggest an inverse relationship between public investment levels and institutional quality, supporting the idea that governments use public investment as a vehicle for rent-seeking or to compensate for the fall in private investment due to the poor business environment. In addition, aid flows, revenues and abundance of natural resources contribute positively to the level of capital spending. The author also finds that high volatility of public investment is associated with a lower quality of governance. An increase in revenues is associated with a reduction in the volatility of capital spending, suggesting that proper macroeconomic management smoothes the investment cycle. Finally, the paper provides some tentative evidence of a positive relationship between institutional quality and the quality of infrastructure.